Elimination of extensive cranioorbitofacial defect after removal of myxofibrosarcoma (G2) with replacement of the hard palate and the alveolar process on the left: clinical case - A. P. Polyakov; A. M. Zaitsev; A. D. Kaprin; M. V. Ratushniy; O. V. Matorin; M. M. Filyushin; I. V. Rebrikova; A. L. Sugaipov; A. V. Mordovsky (Опухоли головы и шеи, 2019)
The study objective is to present the experience of performing extensive cranioorbital resection with subsequent arthroplasty of the hard palate and the dentition of the alveolar process of the maxilla.Materials and methods. In 2018, in the Department of Microsurgery of the P.A. Hertzen Moscow Oncology Research Institute, extensive cranioorbital surgery for recurrent sarcoma of the upper jaw was performed, after the treatment in other clinics. The extensive intervention included the exposure of the dura and the single-stage reconstruction of tissue defect, bone defect of the skull base by using the displaced aponeurotic flap of scalp and microsurgical reconstruction of the soft tissues of the face and mouth left free of the gastro-omental flap. In the early postoperative period, the patient underwent endoprosthesis replacement of the hard palate and alveolar process with a dentition. Results. Extensive intervention with resection of the structures cranioorbital zone and the skull base with a single-stage reconstruction with free gastro-omental flap with subsequent arthroplasty of the hard palate and the alveolar process dental arch allowed to rehabilitate the patient.